Studies on Nuclear Structure and Nuclear Dynamics Using Cb-TDHFB - Ebata, Shuichiro (Frontiers in Physics, 2020)
In this paper, we briefly review the studies on nuclear structure and nuclear dynamics using the Canonical-basis time-dependent Hartree-Fock-Bogoliubov (Cb-TDHFB) theory which is one of the time-dependent mean-field models which deal with nuclear pairing. At first, after a brief introduction of the time-dependent mean-field models, we explain the derivation and the properties of Cb-TDHFB equations. Next, we introduce the methods to study the nuclear linear responses and to simulate the nuclear collision in terms of the time-dependent mean-field models. Then, we display parts of the results obtained by using the time-dependent methods; Electric dipole (E1) excitation mode of ^172Yb which is a heavy and prolate deformed open-shell nucleus, Systematic study of low-energy E1 mode, and Comparison of the simulations of the fusion reactions using time-dependent mean-field models with and without pairing correlation. Finally, we summarize the Cb-TDHFB activities and discuss its perspectives.